Tenancy Law Reform Act and Length of Tenancy Discount: Heterogenous Effects in a West German Household Sample - Benjamin Fuchs; Bernd Fitzenberger (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Compared to other European countries rental apartments dominate the German housing market. Policymakers and a large part of the population alike worry about the amount of affordable living space. Especially in metropolitan areas a high demand for living space exists and has been leading to a shortage and as a consequence to increasing rents. In 2001 the German government passed the Tenancy Law Reform Act to restrict the growth in rents (at least partially) and to strengthen the tenant's position. Up to now the efficacy of this reform has not been examined on national level. A further point of interest is the identification of a length of tenancy discount. The existing literature confirms such a discount where long-term tenants have to pay a lower real valued rent than short-term tenants. Our empirical analysis exploits data from the German Socio-Economic Panel (SOEP) that offers the unique advantage of a large and representative sample. We find that the Tenancy Law Reform Act in 2001 appears to have been successful in the restriction of exorbitant rents. Further, we identify a significant duration discount in the first years of a tenancy. This discount is significantly larger in the upper part of the conditional rent distribution.
Keywords: C21; C23; R30; 330